Biological invasions in forest ecosystems - Liebhold, Andrew M. (2017)
Forests play critical roles in global ecosystem processes and provide numerous services to society. But forests are increasingly affected by a variety of human influences, especially those resulting from biological invasions. Species invading forests include woody and herbaceous plants, many animal species including mammals and invertebrates, as well as a variety of microorganisms such as fungi, oomycetes, bacteria and viruses. These species have diverse ecological roles including primary producers, herbivores, predators, animal pathogens, plant pathogens, decomposers, pollinators and other mutualists. Although most non-native species have negligible effects on forests, a few have profound and often cascading impacts. These impacts include alteration of tree species composition, changes in forest succession, declines in biological diversity, and alteration of nutrient, carbon and water cycles. Many of these result from competition with native species but also trophic influences that may result in major changes in food web structure. Naturally regenerating forests around the world have been substantially altered by invading species but planted forests also are at risk. Non-native tree species are widely planted in many parts of the world for production of wood and fibre, and are chosen because of their frequently exceptional growth in their new environment. This greater growth is due, in part, to escape from herbivores and pathogens that exist in their native ranges. Over time, some pest species can “catch-up” with their hosts, leading to subsequent declines in forest productivity. Other impacts result when native herbivores or pathogens adapt to exotic trees or when novel associations form between pathogens and vectors. Additionally, planted non-native trees are sometimes invasive and can have substantial adverse effects on adjacent natural areas. Management of invasions in forests includes prevention of arrival, eradication of nascent populations, biological control, selection for resistance in host trees, and the use of cultural practices (silviculture and restoration) to minimize invader impacts. In the future, the worlds’ forests are likely to be subject to increasing numbers of invasions, and effective management will require greater international cooperation and interdisciplinary integration.